Polar animals : The incredible animals of the Arctic and Antarctic - Hayes, Susan; Gordon-Harris, Tory (New York : Scholastic, 2014)
Profiles of Arctic and Antarctic animals cover subjects ranging from polar bears and emperor penguins to blue whales and Arctic terns.
Keywords: Penguins polar animals -- Life science -- Informational